Actor–partner association of work–family conflict and parental depressive symptoms during COVID‐19 in China: Does coparenting matter?. Issue 2 (24th October 2021) - Zou, Shengqi; Wu, Xinchun; Ren, Yizhen; Wang, Xinyi
Abstract: Parental depressive symptoms and their related factors have not been widely examined during the COVID‐19 pandemic. Therefore, the current study examined the actor and partner associations of work–family conflict and parental depressive symptoms. Considering the new demands and challenges for families during the COVID‐19 pandemic, we further explored the moderation effect of coparenting. A cross‐sectional online survey with 985 paired fathers and mothers was conducted in Mainland China. In 11.6% of families, only mothers reported moderate to severe depressive symptoms; in 10.6% families, only fathers reported moderate to severe depressive symptoms; in 9.5% families, the mother and father reported mild to moderate depressive symptoms. Results of the actor–partner interdependence model showed that parental family‐to‐work conflict was negatively associated with their own depressive symptoms. The negative actor association of maternal family‐to‐work conflict and depressive symptoms was moderated by undermining coparenting. The partner effects of maternal family‐to‐work and work‐to‐family conflicts on paternal depressive symptoms were moderated by undermining coparenting. Moreover, supportive coparenting moderated the actor association of work‐to‐family conflict and the depressive symptoms of fathers. Results highlight the importance of family‐to‐work conflict and family function for parental depressive symptoms. These findings can help promote parental well‐being during the COVID‐19 pandemic.